Model to predict duty of community nurses in promotive and preventive care - Sismulyanto Sismulyanto; Nursalam Nursalam; Ferry Efendi; Made Mahaguna Putra; Aditha Angga Pratama (Intelektual Pustaka Media Utama, 2019)
Community nurses had important role in promotive and preventive care in community. Aim of the study was to make model to predict community nurses role in promotive and preventive care based on Health Promotion Model (HPM). Design of the study was used explanatory with cross sectional approach. Sum of participant was 161. This study was conducted in 11 Public Health Center in Banyuwangi at 1 January to 30 January 2018. Methods of data collection was cluster sampling. The data was analysed using smartPLS software.. Inner model: personal factors (t=1.981), interpersonal influences (t=4.036), situational influences (5.720), commitment (t=5.138) had affected to community nurses duty in promotive and preventive care. This model could predict community nurses duty in promotive and preventive care in high level (Q=0.998). That was important to enhance of community nurses duty through modifying commitment of nurses, interpersonal influence factors, personal factors and situational influence factors.